Behavior of gravity earth retaining wall - Phan, Xuan Dung. (2009)
For port development, it is sometimes necessary to construct large gravity retaining structures followed by backfilling with sand. Backfilling can induce movements to the retaining wall and induce lateral pressures on the wall which can adversely affect the stability of the wall. The aim of this project is to study and investigate the effects of various key parameters on the behavior of a large retaining wall. The parameters selected in this study are the wall friction, soil properties, different wall shape, seepage, existing slope and uniform surcharge. Analysis involving the use of the finite element method and comparisons with conventional design methods such as Rankine and Coulomb’s method were carried out. The Finite element program PLAXIS was used to compute the soil and wall movements and earth pressures acting on the wall. The finite element analysis results were found to be in good agreement with the conventional design methods. The results indicate that stability of the wall increases together with the wall friction and decreases in case of seepage, existing slope and uniform surcharge. Simple design charts for wall responses i.e. pressure increase on wall side due to uniform surcharge were proposed.